Study On Medical Solid Waste Management Policy At RSIA Yasmin Palangka Raya - M. Mukhlas Roziqin; Ray Kentkhute (International Journal of Science and Environment (IJSE), 2025)
This study aimed to evaluate the policy of solid medical waste management at RSIA Yasmin Palangka Raya. The main issues faced include discrepancies in packaging, collection, storage, and transportation of medical waste. A qualitative descriptive approach was employed using purposive sampling method to collect data through interviews, observations, and document analysis. The research findings revealed that despite the existence of internal policies, there were inconsistencies with the applicable regulations, particularly in waste packaging, segregation, and transportation. The composition of solid medical waste generated included infectious waste, non-sharp infectious waste, and sharp infectious waste. Policy recommendations are suggested to improve waste segregation, staff training, increase transportation frequency, and upgrade storage facilities. By implementing these recommendations, RSIA Yasmin Palangka Raya can enhance the effectiveness of solid medical waste management in accordance with regulations.